The Insiders' Dilemma: An Experiment on Merger Formation - Tobias Lindqvist; Johan Stennek (The Research Institute of Industrial Economics (IUI), 2001)
This paper tests the insiders' dilemma hypothesis in a laboratory experiment. The insiders' dilemma means that a profitable merger does not occur, because it is even more profitable for each firm to unilaterally stand as an outsider (Kamien and Zang, 1990 and 1993). The experimental data provides support for the insiders' dilemma, and thereby for endogenous rather than exogenous merger theory. More surprisingly, our data suggests that fairness considerations also make profitable mergers difficult. Mergers that should occur in equilibrium do not, since they require an unequal split of surplus.
Keywords: C78; C92; G34; L13; L41; 330; Coalition Formation; Experiment; Insiders' Dilemma; Mergers; Antitrust; Fusion; Koalition; Test; Theorie